The The Effect of Book-Tax Differences and Operating Cash Flow on Earnings Persistence with Good Corporate Governance as Moderating Variable - Sukma Halimatus Sa'diyah; Dwi Suhartini (Universitas Sains dan Teknologi Komputer, 2022)
Persistent earning show that the company is able to maintain sustainable profits. With this in mind, this study was conducted to examine and analyze the effect of Permanent Differences, Temporary Differences, and Operating Cash Flows on Profit Persistence moderated by Good Corporate Governance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2015-2019. This study uses secondary data and analyzed using Structural Equation Model based on Partial Least Square. The results of the study show that only temporary differences have a significant effect on earnings persistence and Good Corporate Governance can weaken the relationship between temporary differences and earnings persistence.